2021
DOI: 10.21203/rs.3.rs-693498/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Evaluation of Denosumab And Zoledronic Acid For Medication-Related Osteonecrosis of The Jaw In Patients With Bone Metastases: A Propensity Score-Matched Analysis

Abstract: Purpose: This study evaluated the risk of medication-related osteonecrosis of the jaw (MRONJ) in patients with cancer who received denosumab or zoledronic acid (ZA) for treating bone metastasis.Methods: The medical records of patients were retrospectively reviewed. Patients who did not undergo a dental examination at baseline were excluded. The primary endpoint was a comparison of the risk of developing MRONJ between the denosumab and ZA groups. Propensity score matching was used to control for baseline differ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…(1) It was also reported that the risk of developing ONJ in patients with cancer and bone metastases was significantly higher in the denosumab group than in the zoledronic acid group. (2,3) Teriparatide has been considered an effective therapeutic modality for medication-related ONJ in previous reports. (4)(5)(6) However, there are certain concerns about using teriparatide for the treatment of ONJ and osteoporosis thereafter in patients who have developed denosumab-related ONJ.…”
mentioning
confidence: 99%
“…(1) It was also reported that the risk of developing ONJ in patients with cancer and bone metastases was significantly higher in the denosumab group than in the zoledronic acid group. (2,3) Teriparatide has been considered an effective therapeutic modality for medication-related ONJ in previous reports. (4)(5)(6) However, there are certain concerns about using teriparatide for the treatment of ONJ and osteoporosis thereafter in patients who have developed denosumab-related ONJ.…”
mentioning
confidence: 99%